2007
DOI: 10.1017/s0950268807009120
|View full text |Cite
|
Sign up to set email alerts
|

HIV in gay and bisexual men in the United Kingdom: 25 years of public health surveillance

Abstract: It is more than 25 years since the first case of AIDS was reported in the United Kingdom. In December 1981 a gay man was referred to a London hospital with opportunistic infections indicative of immunosuppression. National surveillance began the following year, in September 1982, with the notification of deaths and clinical reports of AIDS and Kaposi's sarcoma plus laboratory reports of opportunistic infections. Since then epidemiological surveillance systems have evolved, adapting to, and taking advantage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…For example, the 2005–2011 surveillance results showed that the percentage of MSM who had multiple homosexual sexual partners over 6 months increased from 68.0% in 2008 to 85.4% in 2011 [13, 44]. In addition, MSM was not only associated with high-risk behaviours but also with high migration rates, which can increase the number of casual sexual partners [45]. In the present study, multiple sexual partners were negatively associated with years for the floating populations along with downward HIV prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the 2005–2011 surveillance results showed that the percentage of MSM who had multiple homosexual sexual partners over 6 months increased from 68.0% in 2008 to 85.4% in 2011 [13, 44]. In addition, MSM was not only associated with high-risk behaviours but also with high migration rates, which can increase the number of casual sexual partners [45]. In the present study, multiple sexual partners were negatively associated with years for the floating populations along with downward HIV prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…MSM are at high risk for HIV infection in worldwide because of their high partner numbers without protection and high migration rates 4042. Among 30 956 AIDS cases reported among men in the USA in 2005, 53% were MSM.…”
Section: Discussionmentioning
confidence: 99%
“…A major factor in this is likely to be differences between job groups in the prevalence of homosexuality, rates of HIV infection being higher in male homosexuals. [16] A second influence may be the frequency of intravenous drug abuse, shared use of needles being another important route by which the virus is transmitted. [17] Hepatitis B and C can also be transmitted in this way, and this may explain why many of the job groups with high PMRs for HIV/AIDS also had high mortality from viral hepatitis.…”
Section: Discussionmentioning
confidence: 99%